Kualitas Hidup Pasien Gagal Ginjal Kronis yang menjalani Hemodialisis di RSUD Dr. Doris Sylvanus Palangka Raya: Quality of Life of Chronic Kidney Disease Patients on Hemodialysis at Dr. Doris Sylvanus Hospital Palangka Raya - Dewi Sari Mulia; Evi Mulyani; Guntur Satrio Pratomo; Nurul Chusna (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Kidney disease includes various diseases and disorders affecting the kidney function. If not treated immediately then there will be kidney failure. Patients with Chronic Kidney Disease (CKD) require hemodialysis due to impaired endocrine, metabolic, electrolyte and acid-base functions. Hemodialysis is a substitute for kidney function to remove the rest of the metabolism. These hemodialysis actions can affect the quality of life of patients. The purpose of this study was to determine the quality of life of CKG patients undergoing hemodialysis therapy in dr. Doris Sylvanus Hospital Palangka Raya. This research uses the univariate quantitative method with a descriptive approach. Data were collected using a questionnaire adapted from the World Health Organization Quality of Life (WHOQoL)-BREF containing 26 items of questions covering four dimensions: physical, psychological, environmental and social. The sample used in this study as many as 30 people. Based on the assessment of the quality of life in this study showed that physical and psychological dimensions including in moderate quality of life, and environmental and social dimensions including a good quality of life.